Australia's first case of glyphosate-resistant tall fleabane (Conyza sumatrensis) and alternative herbicide options for its control. (3rd December 2022) - Chauhan, Bhagirath S.
Abstract: Tall fleabane is emerging as a problematic weed species in the eastern cropping region of Australia. Recently, growers indicated poor control of tall fleabane to the field rate of glyphosate in fallow fields. Pot studies were conducted in an open field at the Gatton farm of the University of Queensland, Queensland, Australia, to confirm the level of glyphosate resistance in a putative glyphosate-resistant (GR) tall fleabane population and to evaluate the performance of alternative postemergence herbicides to control GR tall fleabane. Compared with a glyphosate-susceptible (GS) population, the level of resistance in the GR population was 4-fold and 3.5-fold greater based on plant survival and biomass, respectively. The target-site resistance mechanism was not present because both the GR and GS populations had the same gene sequence. There were several effective alternative herbicides for the control of small (4-leaf stage) plants of tall fleabane, but to control large (12- to 14-leaf stage) plants, the sole application of saflufenacil + trifludimoxazin or its mixtures with glyphosate, glufosinate, or paraquat were the best herbicide treatments. This is the first published report on the occurrence of GR tall fleabane in Australia. Growers need to use integrated management strategies to mitigate the further spread of GR tall fleabane in fallow fields as well as glyphosate-resistant crops.